Effect of aeration on growth and production of fish in intensive aquaculture system in earthen ponds - Sultana, T; Haque, MM; Salam, MA; Alam, MM (Journal of the Bangladesh Agricultural University, 2017)
An experiment was conducted to assess the effect of aeration using blower on growth and production of tilapia (Oreochromis niloticus) in intensive aquaculture system in six (6) earthen ponds at BAU campus, Mymensingh from May to September, 2016. Treatment 1 (T1) with 3 aerated ponds and Treatment 2 (T2) with 3 non-aerated ponds were designed with similar stocking density (300/decimal) of tilapia. Oxygen supply was ensured by blower for 9 hours daily when oxygen depletion occurs in pond water. Fish growth, pond water and soil quality parameters were sampled and assessed. The DO content in the aerated ponds was higher (7.23 mg/l) from the beginning to the end of experiment compared to non-aerated ponds (2.33 mg/l). There were significant differences (p<0.05) of DO content between two treatments at first and last sampling stages. The higher length (15.64±1.56 cm) and weight gain (143.36±39.33 gm), higher SGR (% per day) for tilapia was (2.54±0.00) found in T1 compared to T2 (2.42±0.00) with significant differences (p<0.05) between two treatments. In addition, the higher production of tilapia was obtained in T1 (9581.87±0.00 kg/ha/100 days) compared to T2 (6490.80±0.00 kg/ha/100 days). The average phytoplankton production was relatively higher in T2 and conversely zooplankton abundance was higher in T1 without any significant differences (p>0.05) between the treatments for the abundances of various groups of phytoplankton and zooplankton. Different water quality parameters were found with the better range in aerated ponds. Various intrinsic relationships between DO and other water quality and weather parameters showed that DO content had negative relationships with rainfall, air pressure and humidity but the relationships were not statistically significant. Moreover, different soil quality parameters of pond sediments were found in ideal range for fish culture in both treatments. These results suggest that aeration can be a potential mechanism of aqua-farming to enhance the growth and production of tilapia and DO content in pond water synchronizing other water quality parameters in ponds. J. Bangladesh Agril. Univ. 15(1): 113-122, January 2017